Kewajiban Moral, Keadilan Pajak, dan Kepercayaan pada Pemerintah terhadap Kepatuhan Wajib Pajak - Annisa, Ishma; Suparna Wijaya (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the variables that affect taxpayer compliance such as moral obligations, tax fairness, and trust in government among MSMEs in DKI Jakarta. Methodology: This study used a quantitative methodology to assess variables related to research through respondent questionnaires about tax compliance to MSME’s in DKI Jakarta. Using statistical software SmartPLS 4.0, data were analysed using PLS-SEM techniques with outer and inner models. Results: Moral obligation, tax fairness, and trust in government variables comprise the 23 items that contain the variable dimensions used to assess the validity of their effects on purchasing decisions. The results show that moral obligation affects taxpayer compliance. Meanwhile, tax fairness and trust in government do not affect taxpayer compliance among MSMEs in DKI Jakarta. Limitations: The limitations of this research include the variables used, a limited number of respondents which prevents the results from being generalized, and the potential for biased results due to the use of questionnaires for data collection. Contribution: This research is intended to provide an evaluation for the government to enhance public trust and tax fairness and broaden readers' understanding.